System identification and control parameter optimization for a stylus profiler with exchangeable cantilevers - Felix Ströer; Katharina Trinkaus; Indek Raid; Jörg Seewig (Engineering Science and Technology, an International Journal, 2018)
Stylus instruments are widely used in production metrology due to their robustness. Interchangeable cantilevers allow a wide range of measuring tasks to be covered with one measuring device. When approaching the sample, the positioning of the stylus instrument tip relative to the measurement object has to be accomplished in a controlled way in order to prevent damages to the specimen and the stylus cantilever. This is achieved by a closed-loop control. We present a method for the objective description of the stylus cantilever dynamics with system-theoretical techniques and show a simple iterative approach to optimize closed-loop control parameters with boundary conditions.